A world of architecture - Byrnes, Richard A.; Dhalby, Jack; Double Diamond Corporation; Lucerne Media (Morris Plains, NJ : Lucerne Media, 1994)
Introduction to architecture and its many styles, filmed on location at sites both ancient and modern. Students learn how technology from stone on stone to steel and glass to inflatable buildings has been used to shape our public and private spaces. Key examples from prehistory to the present help students entify the major styles and periods
Executive producer, Richard A. Byrnes
Narrator : Jack Dhalby
Keywords: Architecture; Architecture -- History